Long-Term Impacts of Defoliator Outbreaks on Larch Xylem Structure and Tree-Ring Biomass - Castagneri, Daniele; Prendin, Angela L.; Peters, Richard L.; Carrer, Marco; von Arx, Georg; Fonti, Patrick (Frontiers in Plant Science, 2020)
Defoliator insects are a major disturbance agent in many forests worldwide. During outbreaks, they can strongly reduce photosynthetic carbon uptake and impact tree growth. In the Alps, larch budmoth (Zeiraphera diniana) outbreaks affect European larch (Larix decidua) radial growth over several years. However, immediate and legacy effects on xylem formation, structure and functionality are still largely unknown. In this study, we aimed at assessing the impact of budmoth defoliations on larch xylem anatomical features and tree-ring structure. Analyses were performed in the Lötschental (Swiss Alps) within (1900 m a.s.l.) and above (2200 m a.s.l.) the optimum elevational range of larch budmoth. We investigated variability of xylem anatomical traits along century-long tree-ring series of larch (host) and Norway spruce (non-host) trees. We identified eight outbreaks affecting larch xylem anatomy during the 20th century, particularly at 1900 m. Tracheid number always showed a higher percent reduction than properties of individual cells. Cell lumen size was slightly reduced in the first 2-3 years of outbreaks, especially in the early part of the ring. The more carbon-demanding cell wall was thinned along the entire ring, but more evidently in the last part. Theoretical tree-ring hydraulic conductivity was reduced for several years (up to 6), mostly due to cell number decrease. Reduced cell wall area and cell number resulted in a strong reduction of the tree-ring biomass, especially in the first year of outbreak. Our study shows that, under carbon source limitations caused by natural defoliation, cell division is more impacted than wall thickening and cell enlargement (the least affected process). Consequences on both xylem hydraulic properties and tree-ring biomass should be considered when assessing long-term defoliator effects on xylem functioning, forest dynamics, and terrestrial carbon cycle.